2010
DOI: 10.1111/j.1742-4658.2010.07704.x
|View full text |Cite
|
Sign up to set email alerts
|

Novel strategy for protein production using a peptide tag derived from Bacillus thuringiensis Cry4Aa

Abstract: Numerous proteins cannot be sufficiently prepared by ordinary recombinant DNA techniques because they are unstable or have deleterious effects on the host cell. One idea to prepare such proteins is to produce them as protein inclusions. Here we developed a novel system to effectively prepare proteins by using peptide tags derived from the insecticidal Cry toxin of a soil bacterium, Bacillus thuringiensis. Fusion with this peptide tag, designated 4AaCter, facilitates the formation of protein inclusions of gluta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 21 publications
0
19
0
Order By: Relevance
“…Hayakawa et al [14] used a peptide tag derived from the C-terminal half of the Cry4Aa protoxin (amino acids 696–851) to enhance the production and purification of functional TpN protein [14]. …”
Section: Introductionmentioning
confidence: 99%
“…Hayakawa et al [14] used a peptide tag derived from the C-terminal half of the Cry4Aa protoxin (amino acids 696–851) to enhance the production and purification of functional TpN protein [14]. …”
Section: Introductionmentioning
confidence: 99%
“…4AaCter is a polypeptide of 156 residues in length, derived from the C‐terminal region of the insecticidal Cry4Aa toxin of a soil bacterium, Bacillus thuringiensis [24, 45]. The Cry4Aa toxin normally forms protein crystals, which is mediated by its C‐terminal region, or blocks 6 and 7 of the protein [24]. The protein crystal solubilizes in the dipteran midgut alkali fluid and yields the active toxin after digestion by midgut proteases [45].…”
Section: Purification Tags That Induce Active Protein Aggregates Inmentioning
confidence: 99%
“…The protein crystal solubilizes in the dipteran midgut alkali fluid and yields the active toxin after digestion by midgut proteases [45]. The Sakai group found that the 4AaCter tag was able to push a number of target proteins (including glutathione S‐transferase (GST), syphilis antigens TpN15, TpN17 and TpN47) into protein aggregates upon expression in E. coli [24]. Proteins in these aggregates were likely to be active, although no measurement of activity for these protein aggregates was reported [24].…”
Section: Purification Tags That Induce Active Protein Aggregates Inmentioning
confidence: 99%
See 2 more Smart Citations